THE EFFECT OF PROFITABILITY, LEVERAGE, COMPANY SIZE AND MANAGERIAL OWNERSHIP ON ACCOUNTING CONSERVATISM (Empirical Study of Manufacturing Firms Listed on the Indonesia Stock Exchange for the Period 2017-2020) - Andini Yulianti; Nursiam Nursiam (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this research is to examine the influence of profitability, leverage, fiirm size, and managerial ownership on accounting conservatism. This research uses quantitative methods and secondary data. The population in this research are manufacturing industry firm listed on the Indonesian Stock Exchange (IDX) in 2017-2020. The sample used on this research was 128 with a samplng technque using purposive sampling method. . The analytical technique used on this study is classical assumption test, multiple linear regression analysis, and hypothesis testing. The outcome of the research declare that profitability and managerial ownershop are affects accounting conservatism. Meanwhile, leverage and company size do not affect the accounting conservatism.